Effect of plasma jet on the water and hydrogen peroxide that used for assisted teeth bleaching - Humud, Hammad R. (Iraqi Journal of Physics, 2019)
In this work the interaction of plasma jet with water and hydrogen peroxide liquids used for assisted teeth bleaching by plasma jet had been study. A homemade plasma jet system was used. The plasma jet supply by 15 W electrical power generated by high voltage power supply of 9.6 kV peak to peak and frequency of 33 kHz .this power supply generate high electric field on electrodes that would be enough to ionize the argon gas. Some important agents were study such as the effect of the Ar gas flow rates on the length of the plasma jet, the influence of plasma jet on some properties of water and two hydrogen peroxide concentrations 25 % and 30 % like pH, conductivity and liquid temperature for different exposure time. The liquids temperature was measured by digital infrared thermometer, the gas flow rate were measured by gas flow meter, the pH, and the conductivity was measured by pH conductivity ultra-meter. The results illustrated that the conductivity and liquid temperature increase with increasing of exposure time. It can be conclude that the liquid properties were changed less than the boundaries that could affect adversely to the cells that located in the plasma jet.